Biological roles of adenine methylation in RNA - Boulias, Konstantinos; Greer, Eric Lieberman (Nature reviews. Genetics, 2023)
N -Methyladenosine (m A) is one of the most abundant modifications of the epitranscriptome and is found in cellular RNAs across all kingdoms of life. Advances in detection and mapping methods have improved our understanding of the effects of m A on mRNA fate and ribosomal RNA function, and have uncovered novel functional roles in virtually every species of RNA. In this Review, we explore the latest studies revealing roles for m A-modified RNAs in chromatin architecture, transcriptional regulation and genome stability. We also summarize m A functions in biological processes such as stem-cell renewal and differentiation, brain function, immunity and cancer progression.